Multidisciplinary simulation of local anaesthetic systemic toxicity improves diagnostic and treatment skills and self-confidence for pain clinic procedural staff - Kevin Vorenkamp; Robert Ackerman; Matthew Riley; Muhammad A Farooq Anwar; Duran Mitchell; Ankeet Udani; Peter Yi (BMJ Open Quality)
Format Small group didactic session, simulation exercise in a clinical simulation lab.Target audience Attending, fellow, and resident physicians, medical students, registered nurses, certified medical assistants, and radiation technologists working in a pain clinic procedure suite.Objectives To acquaint the pain clinic procedural staff with current training related to LAST and an opportunity to practice in a controlled environment.